Dental Implant Placement with Simultaneous Anterior Maxillary Reconstruction with Block and Particulate Fresh Frozen Allograft Bone: A Case Report with 24-Month Follow-Up Data - J. S. Vieira; E. M. Brandão-Filho; F. R. Deliberador; J. C. Zielak; A. F. Giovanini; T. M. Deliberador (Case Reports in Surgery)
Fresh frozen allograft bone is routinely used in orthopedic surgery for the reconstruction of large bone defects, and its use in oral and maxillofacial surgery is increasing. The purpose of this case was to demonstrate the installation of dental implants and the use of fresh frozen bone for reconstruction of anterior maxilla in the same surgery. This case report presents the insertion of dental implants followed immediately by a placement of fresh frozen allograft in block and particle for a reconstruction of atrophic anterior maxillary in the same surgery. Ten months subsequent to this procedure, provisional fixed prosthesis was installed on the implants. Four months later (postoperative month 14), the final fixed prosthesis was installed and the clinical success was observed. The insertion of dental implants followed immediately by a placement of fresh frozen allograft is a safe and efficient process that results in the successful return of dental function and aesthetic rehabilitation for the patient.